Relationship between earnings per share (EPS) and bank performance in Malaysia / Yasmin Yussof - Yussof, Yasmin (2016)
The purpose of this research paper is to evaluate the relationship between earning per share (EPS) and bank's profitability in Malaysia . The data of the study was collected from annual financial statements of 5 commercial banks working in Malaysia covering the period of 8 years from 2007 to 2013. Pearson Correlation has been used to find the relationship and simple regression method has been employed to evaluate the impact of earning per Share (EPS) on bank's profitability. All hypotheses mentioned in the study were accepted. Findings revealed that all independent variables have strong relationship between dependent variable.